Predictive utility of the ages and stages questionnaire for below average cognitive ability at age 5. (20th October 2021) - Bowe, A; Staines, A; Murray, D
Abstract: Background: The first 1000 days of life are a period of unique sensitivity and plasticity during which critical cognitive abilities are formed. For children at risk of later cognitive difficulties, this period is the ideal target for early intervention initiatives. Routine developmental screening tools aim to identify infants who would benefit from early intervention. While these tools have been validated for detecting children with more severe neurodevelopmental disorders, their ability to identify the larger proportion with below average cognitive ability has not been sufficiently explored. The aim of this study was to examine the predictive utility of the Ages and Stages Questionnaire (ASQ), for identifying children with later below average cognitive function. Methods: The study population (n = 8260) is formed from two national cohort studies, the Growing Up in Ireland Infant cohort (n = 7, 444) and the Cork BASELINE cohort (n = 816). The ASQ was completed at 8- and 24-months respectively. Cognitive assessments were performed at age 5. Those scoring <1 standard deviation below the mean were categorised as below average cognitive ability. Applying the currently used onward referral criterion (one fail in any domain) the sensitivity, specificity, positive and negative predictive values of the 8- and 24-month ASQ for detecting children with later below average cognitive function were calculated. Results: The sensitivities of the 8-month and 24-month ASQ for detecting children with below average cognitive ability were 16.4% (95% CI 14.0-19.0) and 20.8% (95% CI 13.6-30.2) respectively, with specificity of 92.0% (95% CI 91.3-92.6) and 91.1% (95% CI 88.6-93.2). Conclusions: The ASQ has a low sensitivity for identifying children with below average cognitive ability at age 5. The findings of this study suggest that if we are to intervene early in the developmental trajectory for children with below average cognitive ability alternative methods of identifying high risk infants are needed. Key messages: The ages and stages questionnaire, a widely used routine infant developmental screening tool, has a low sensitivity between 16%-21% for detecting later below average cognitive ability. To enable intervention in the first 1000 days of life for children at risk of later below average cognitive ability alternative methods of screening and risk identification require investigation.